An unfinished life - Spragg, Mark, 1952-; Spragg, Virginia Korus; Redford, Robert; Lopez, Jennifer, 1970-; Freeman, Morgan; Lucas, Josh.; Lewis, Damian, 1971-; Gardner, Becca; Miramax Films; Revolution Studios; Initial Entertainment Group (Burbank, CA : Miramax Home Entertainment : Distributed by Buena Vista Home Entertainment, 2006)
Einar is a crusty old rancher who does what he can to hold onto his Wyoming ranch. It's been a struggle for years; his son was killed in a car crash, his wife left him, and his longtime friend and helper, Mitch was recently mauled by a bear. Now, Einar has to care for Mitch and help him recover. Jean and her daughter, Griff, have to leave Jean's current abusive boyfriend. The only place they can go is the ranch of Griff's grandfather, Einar, who only learns of his granddaughter's existence upon their arrival.
Widescreen edition.
[Typographic symbols and accents removed for systems compatibility.]
Director of photography, Oliver Stapleton ; art directors, Karen Schulz Gropman, James Steuart ; editor, Andrew Mondshein ; costume designer, Tish Monaghan ; production designer, David Gropman.
Robert Redford, Jennifer Lopez, Morgan Freeman, Josh Lucas, Camryn Manheim, Damian Lewis, Becca Gardner.
MPAA rating: PG-13; for some violence including domestic abuse, and language.
DVD; widescreen version; region 1; Dolby Digital.
Keywords: Ranchers -- Wyoming -- Drama; Grandparent and child -- Wyoming -- Drama; Mothers and daughters -- Wyoming -- Drama; Feature films; Video recordings for the hearing impaired; Western films; Melodramas (Motion pictures).